Estudio sociojurídico de los abogados en libre ejercicio profesionalEl caso ecuatoriano - Moscoso Guerrero, Inés Melina (2018)
Resumen:Socio-legal studies of independent lawyers the Ecuadorian case, aims to analyze the institutions and the cognitive dispositions that defines subfield of independent lawyers within the Ecuadorian legal system, in order to have this analysis done a survey applied to independent lawyers in the city of Cuenca was carried out, which enabled to have solid results in aspects related to their early formative and work experiences, as well as their perception towards the Ecuadorian legal system and their professional and political participation. The present research work made it possible to observe, mainly, that academic programs related to Law Studies must go through deep challenges and changes, in order to meet the social demands related to formal education within this field.